STRATEGI PENYULUH BAHASA BALI DALAM MENINGKATKAN KETERAMPILAN BERBAHASA BALI PADA SISWA SEKOLAH DASAR DI DESA BESTALA BULELENG - Ketut Sidang Partayasa; Ni Nengah Selasih; I Ketut Sudarsana (Pangkaja: Jurnal Agama Hindu, 2021)
Balinese was one of the local languages that needed to be preserved. To preserve them requires the planting of understanding that starts with children. The Balinese language lesson got into the local content, so the Balinese study was short. Given matter does not fit the field of possession. The Balinese textbook was also very scant, and the teacher was a class teacher rather than a field teacher. It is to be the student of sd Bestala. Students in the possession of language materials, the characters and literature of Bali are not at maximum. On the basis of this, the Bali language education program with the Balinese learning group provides an additional Balinese lesson outside school hours. In general, the aim of the study is to learn Balinese will be able to improve the Balinese ability of Bestala elementary students, silirite district, buleleng district. Specifically assessed: 1. The upgrade of the grade school student Balinese language skills at Bestala village, 2. The process of learning Balinese in meningthe Balinese language skills at Bestala village, and 3. The implication of the Balinese skills on elementary students in Bestala village. As for the theories used in this study are structural functional theories, constructive theories and behavioristic.